Methylome-wide change associated with response to electroconvulsive therapy in depressed patients - Sirignano, Lea; Frank, Josef; Kranaster, Laura; Witt, Stephanie; Streit, Fabian; Zillich, Lea; Sartorius, Alexander; Rietschel, Marcella; Foo, Jerome Clifford (Translational Psychiatry, 2021)
Electroconvulsive therapy (ECT) is a quick-acting and powerful antidepressant treatment considered to be effective in treating severe and pharmacotherapy-resistant forms of depression. Recent studies have suggested that epigenetic mechanisms can mediate treatment response and investigations about the relationship between the effects of ECT and DNA methylation have so far largely taken candidate approaches. In the present study, we examined the effects of ECT on the methylome associated with response in depressed patients (n = 34), testing for differentially methylated CpG sites before the first and after the last ECT treatment. We identified one differentially methylated CpG site associated with the effect of ECT response (defined as >50% decrease in Hamilton Depression Rating Scale score, HDRS), TNKS (q < 0.05; p = 7.15 × 10−8). When defining response continuously (ΔHDRS), the top suggestive differentially methylated CpG site was in FKBP5 (p = 3.94 × 10−7). Regional analyses identified two differentially methylated regions on chromosomes 8 (Šídák’s p = 0.0031) and 20 (Šídák’s p = 4.2 × 10−5) associated with ΔHDRS. Functional pathway analysis did not identify any significant pathways. A confirmatory look at candidates previously proposed to be involved in ECT mechanisms found CpG sites associated with response only at the nominally significant level (p < 0.05). Despite the limited sample size, the present study was able to identify epigenetic change associated with ECT response suggesting that this approach, especially when involving larger samples, has the potential to inform the study of mechanisms involved in ECT and severe and treatment-resistant depression.
Gesehen am 18.10.2021